Islam, the people and the state political ideas and movements in the Middle East - Zubaida, Sami, 1937- (I.B.Tauris, 2001)
The recent prominence of Islamic politics in the Middle East, notably the Iranian revolution and its ramifications, has raised important questions about society, politics and culture. It has posed a challenge to the main theoretical approaches in the social sciences from Marxism to modernization theory and it has given some credence to the idea that the world of Islam is essentially distinct from Europe, and follows a course of development dictated by its own history and culture. In this book, Sami Zubaida challenges these diverse opinions in favour of a general political sociology capable of dealing with the historical and cultural personalities of societies and situations in the region. He argues that rather than being "revivals" of historical ideas and institutions, current political and social developments in the Islamic World are, in fact, uniquely modern phenomena.